Physical Activity and Associated Factors among Patients Attending Hypertension Clinics in Mbarara City, Southwestern Uganda - Atwongyeire Night; Ssewanyana Anna Maria; Namukwaya Racheal; Mutesasira Edward; JJunju Fred; Nuwahereza Amon; Jean Damascene Niyonsenga; Zillah Whitehouse; Kazibwe Herman; Arubaku Wilfred (medRxiv, 2023)
Background: Physical activity has been shown to prevent mortality and morbidity among people with hypertension. Hypertension has been identified to affect about 33% of the adult population across the globe and 26.4% in Uganda. An increase in hypertension and its adverse outcomes have been observed and reported in Southwestern Uganda. This may be due to physical inactivity. However, there is limited evidence demonstrating physical activity among patients with hypertension within Southwestern Uganda. The current study investigated the extent of physical activity and associated factors among patients attending hypertension clinics in Mbarara City, Southwestern Uganda. Objective: To investigate the extent of physical activity and associated factors among patients attending hypertension clinics in Mbarara City, Southwestern Uganda. Methods: A descriptive, quantitative cross-sectional study was conducted. Participants’ data was obtained using a structured researcher-administered questionnaire consisting of the International Physical Activity Questionnaire (IPAQ) long form, Motivation for Physical Activity Questionnaire (RM4-FM) and the Barrier to Being Active Quiz (BBAQ). Frequency distribution tables, Fischer’s exact test and multivariate logistic regression were used to describe data and establish associations during data analysis. A p-value less than 0.05 with 95% confidence interval was considered to be statistically significant. Results: Less than half of the participants (45.39%) were found to be physically active. Level of education, having heard of physical activity, place of residence, sedentary behaviour and social influence were associated with physical activity with the Fischer’s exact test (p-value=0.018) and sedentary behaviour (aOR=0.276; CI=0.126-0.606; p-value=0.001) remained significant factors associated with physical activity. Majority of those who were active reported to be autonomously motivated. Most reported barriers were lack of skill, social influence and lack of willpower. Conclusion: More than half of the patients with hypertension were physically inactive and almost half were inactive and sedentary. This is a double disaster especially for patients with hypertension; therefore, emphasis should be put on educating the public about the benefits of physical activity and availing a variety of physical activity options that engage all demographic groups.
Keywords: Physical activity; Hypertension; Sedentary behaviour